Behaviour of reinforced concrete beam with hybrid fibres subjected to cyclic loading - Muthuswamy, K.R.; Thirugnanam, G.S. (Journal of Structural Engineering, 2024)
The main requirements of disaster resistant structures are good ductility and energy absorption capacity. Fibre reinforced concrete is one which possesses high tensile and flexural strength, improved ductility and high energy absorption capacity than the conventional concrete against dynamic loads. The use of hybrid fibres in the concrete mixture can produce a composite with better engineering properties than that of individual fibres in concrete. This paper deals with the experimental study on the flexural behavior of High Performance Hybrid Fibre Reinforced Concrete beams cast with steel and glass fibres subjected to cyclic loading. The various parameters such as load carrying capacity, stiffness degradation, ductility characteristics and energy absorption capacity of HPHFRC beams were compared with that of RCC beam. It has been observed that the high performance hybrid fibre reinforced concrete beam performs well in flexure when compared to concrete beams with mono fibre and without fibre. The combination of different types of fibres increases the ductility and energy absorption capacity significantly. Also the presence of hybrid fibres helps in reducing the crack width and causes lesser damages to the beams.